Pengelolaan Sarana dan Prasarana Olahraga - Achmad Gunawan; Ika Rudi Mahendra; Abdurrahim Hidayat (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
Sports facilities that are not well managed could hamper the efforts to increase sports achievement and broaden sports culture. It needs an in-depth overview of what causes the sports facilities are not properly managed, as a basis for future management policy considerations. Applying case studies at sports venues in five provinces, including Riau, South Sumatra, West Java, East Kalimantan, and DKI Jakarta, this research aims to delve deeper into the problem of managing sports facilities. The framework concept of Schwarz et al. is used as a theoretical foundation, which is then supplemented by a practical framework based on the concepts of the sports facility growth in Australia, as well as a framework for sport facility development in New Zealand. The researcher uses a qualitative approach because it seeks the answer of how to manage sport facilities. The data are secondary data from monitoring and assessing the outcomes in the field, as well as other related documents. The researcher hopes to figure out the real problem by juxtaposing multiple problems from each province. Thus, it can be found that there are no further considerations regarding the development of sports facilities, there is no connection with the sports culture of the community with the availability of facilities, and there is no link between the availability of facilities with the provincial sports achievements where the center of facilities is located. For the conclusion, it was discovered that the issue of poorly maintained facilities and inadequate utilization, is due to insufficient planning for the development of facilities by paying attention to the sports culture of the local community, the potential for sports event movements, and integration with other fields such as accessibility, tourism, and other community services.